Evaluasi Pelayanan Persalinan oleh Bidan Desa Selama Pelaksanaan Program Jaminan Persalinan di Puskesmas Salomekko Kabupaten Bone Sulawesi Selatan Tahun 2012 - Zulaeha Amirudin Amdadi; Chriswardani Suryawati; Cahya Tri Purnami (Center for Health Policy and Management, 2012)
Background: The delivery assurance (Jampersal) issued from April 2011 aims to increase access to maternal delivery assistance by health workers in health facilities by providing financing guarantees. Delivery coverage by health workers in Bone District in 2011 was 76.67%. Delivery by health workers was only 60% done in health facilities and Salomekko Health Center had the lowest figure which was 25%. Objective: To evaluate service delivery by village midwives during the implementation of Jampersal in Salomekko Health Center of Bone District of South Sulawesi Province in 2012. Methods: This study was observational using a qualitative descriptive design that was evaluative in nature. The study subjects were 8 village midwives in the work area of Salomekko Health Center. The triangulation informants were the head and midwife coordinator of Salomekko Health Center and the head of MCH section of Bone Health office. Data was collected by in-depth interviews and analyzed by content analysis. Results: All midwives in the village did not perform service delivery well because most of them had not joined APN training. There was no Standard Operational Procedures (SOP), four village health post buildings in the four villages were not adequate (their width, no water or electricity and away from settlements), four other villages had not yet Poskesdes, and delivery equipment was also incomplete. The process of planning, implementation, monitoring and supervision of Jampersal was also not performed well. In 2011 and 2012 (January to April), all deliveries by health workers in the Salomekko Health Center were funded by Jampersal although deliveries took place in non-medical facilities. The culture of siri was expected to encourage mothers to give birth at home. The delivery rate by traditional birth attendants was still high. Although there was no necessity, the mothers should pay around 100,000 00 to midwives for consumables without the knowledge of the health office. The application procedure for Jampersal funds with certain administrative requirements was perceived to be quite complicated. Conclusion: Poskesdes needs to be built immediately in four villages and, for the other four villages that already have Poskesdes, the facilities need improving following the completeness of equipment. APN training and Jampersal SOP socialization should be improved and monitoring and supervision by the health center in the village should be increased. Levies should be removed and delivery by health workers not at the health facilities cannot claim Jampersal. Lastly, the claims of Jampersal process should be simplified. Latar belakang: Jaminan persalinan diberlakukan mulai April tahun 2011 dan bertujuan meningkatkan akses ibu bersalin terhadap pertolongan persalinan oleh tenaga kesehatan di fasilitas kesehatan dengan memberikan jaminan pembiaya- annya. Cakupan persalinan oleh tenaga kesehatan di Kabupaten Bone tahun 2011 yaitu 76,67%. Persalinan oleh tenaga kese- hatan hanya 60% dilakukan oleh fasilitas kesehatan dan Puskesmas Salomekko mempunyai angka terendah yaitu 25%. Tujuan penelitian adalah melakukan evaluasi pelayanan persalinan oleh bidan di desa selama pelaksanaan Jampersal di Puskesmas Salomekko Kabupaten Bone Sulawesi Selatan tahun 2012. Metode: penelitian observasional menggunakan rancangan deskriptif kualitatif yang bersifat evaluatif, dengan subyek penelitian adalah 8 orang bidan di desa di wilayah Puskesmas Salomekko. Informan triangulasi adalah Kepala Puskesmas Salomekko dan Bidan koordinator Puskesmas Salomekko, serta Kepala seksi KIA Dinas Kesehatan Kabupaten Bone. Data dikumpulkan dengan wawancara mendalam dan dianalisis dengan content analysis. Hasil: Semua informan bidan di desa belum melaksanakan pelayanan persalinan dengan baik karena sebagian besar petugas belum mengikuti pelatihan APN, belum adanya Standar Operational Prosedur (SOP), empat gedung Pos Kesehatan Desa di empat desa tidak memadai (luasnya, tidak ada air mau- pun listrik dan jauh dari pemukiman), empat desa lainnya belum memiliki Poskesdes, peralatan persalinan juga belum lengkap. Proses perencanaan, pelaksanaan, monitoring dan pengawas- an Jampersal juga belum terlaksana dengan baik. Tahun 2011 dan 2012 (Januari sampai April) semua persalinan oleh tenaga kesehatan di wilayah Puskesmas Salomekko dibiayai dana Jam- persal walaupun persalinan dilakukan di non fasilitas kese- hatan. Budaya siri diperkirakan mendorong ibu bersalin di rumah. Angka persalinan oleh dukun bayi masih tinggi. Walaupun tidak ada keharusan tetapi cukup memberatkan ternyata sebagian ibu bersalin membayar sekitar Rp100.000,00 ke bidan di desa untuk bahan habis pakai, dan hal ini tidak sepengetahuan dinas kesehatan. Prosedur pengajuan dana Jampersal dengan syarat administrasi tertentu dirasakan cukup rumit. Kesimpulan: Diperlukan segera pembangunan Poskesdes di empat desa dan perbaikan fasilitas di empat desa yang telah mempunyai Poskesdes berikut kelengkapan peralatannya, pelatihan APN dan sosialisasi SOP Jampersal begitu juga peningkatan upaya monitoring dan supervisi oleh Puskesmas berdasarkan rayon wilayah desa, menghilangkan pungutan, persalinan Nakes tidak di Faskes tidak diklaimkan jampersal serta penyederhanaan proses klaim Jampersal.